THE IMPLEMENTATION OF SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) LEARNING TO IMPROVE BASIC ASKING SKILLS AND LEARNING ACHIEVEMENTS STUDENTS OF ELEMENTARY SCHOOL - Mufidah, Ilma Aulia (STAI Hubbulwathan Duri, 2019)
This study aims to improve basic questioning skills and student achievement through learning based on science, technology, engineering, and mathematics (STEM). This is a classroom action research that carried out in two cycles, each cycle consisting of two meetings. The subjects of this research were 30 fourth grade students. The data collection tool used evaluation tests, observation sheets for teacher and student activities, and observation sheets for students' basic questioning skills. The results showed that the application of STEM learning can improve students' basic questioning skills from the first cycle with an average of 2.48 to 4.45 in the second cycle. Students' mastery learning presentation also increased every cycle, from 70.44% to 96.66% for science lessons and 78.94% to 96.66% for Indonesian language lessons. The application of STEM-based learning gives good results and learning activities take place actively and pleasantly.